Screening for retinopathy of prematurity in Ibadan (1998)
Between January to June 1995, a prospective study was carried out to determine the incidence and severity of retinopathy of prematurity (ROP) in newborn infants of less than 1,500g birthweight or less than 31 weeks gestational age. 18 babies were eligible for inclusion in this study and only one developed ROP, a Stage 1, Zone III disease i.e. 5.5% of babies at risk. In spite of the low incidence compared with other studies', it is advisable to continue the collaboration between opthalmologists and neonatologists to prevent babies at risk from developing untreatable ROP, thereby increasing the number of blind children in our society.